2001
DOI: 10.1111/1467-9760.00128
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Democracy: Generalizing the Condorcet Jury Theorem

Abstract: Classical debates, recently rejoined, rage over the question of whether we want our political outcomes to be right or whether we want them to be fair.Democracy can be (and has been) justified in either way, or both at once.For epistemic democrats, the aim of democracy is to "track the truth." 1 For them, democracy is more desirable than alternative forms of decision-making because, and insofar as, it does that. One democratic decision rule is more desirable than another according to that same standard, so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
218
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 415 publications
(224 citation statements)
references
References 31 publications
2
218
0
4
Order By: Relevance
“…The P best of the teams is higher than the P best of each one of the agents, and is higher for a team of 6 agents than for a team of 4 agents. This result is expected when we consider the extended version of the Condorcet's Jury Theorem [2], at least for a uniform team. According to the theorem P best approaches 1 when the number of agents goes to infinity.…”
Section: Experiments In Computer Gomentioning
confidence: 68%
See 3 more Smart Citations
“…The P best of the teams is higher than the P best of each one of the agents, and is higher for a team of 6 agents than for a team of 4 agents. This result is expected when we consider the extended version of the Condorcet's Jury Theorem [2], at least for a uniform team. According to the theorem P best approaches 1 when the number of agents goes to infinity.…”
Section: Experiments In Computer Gomentioning
confidence: 68%
“…According to the theorem, when facing a binary decision, as long as the average of the probability of each individual being correct is higher than 1 2 , a group of independent individuals doing plurality voting will have a higher probability of being correct than the individuals alone. This theorem is extended to the k options case in [2], where it is shown that if each of the individuals have a probability of choosing the best answer higher than choosing any other answer, the group performing plurality voting will be stronger than the individuals alone. These theorems, however, do not present any benefits in having diverse agents.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In a system of voting agents, however, disagreements are inherent in the coordination process and do not necessarily mean that an erroneous situation has occurred due to such malfunction. Additionally, research in social choice is mostly focused on studying the guarantees of finding the optimal choice given a noise model for the agents and a voting rule [14,19,49], but provide no help in assessing the performance of a team of voting agents.…”
Section: Introductionmentioning
confidence: 99%